Arrhythmias And Long-Term Hemodynamic Consequences In Patient With Repaired Tetralogy Of Fallot – A Case Study - Rutkowski, Kacper; Kołodzińska, Agnieszka; Koźluk, Edward; Budnik, Monika; Opolski, Grzegorz; Grabowski, Marcin (Journal of Education, Health and Sport, 2023)
The number of patients who underwent total correction of Tetralogy of Fallot (ToF) in early life or infancy is still rising. According to CDC ToF is the most prevalent cyanotic congenital heart disease with incidences of 1 in 2500 births. Rhythm disturbances and haemodynamic disturbances including valves disorders, heart failure, residual defects and more are new challenges for clinicians taking care of adult patients with repaired ToF. Our goal was to describe such a patient and highlight further complications which may be encountered among those patients.